CONSIDERING THE METHODOLOGICAL COMPLEXITIES OF THE INTERVIEW APPROACH WHEN EXPLORING THE WORK OF MOTHERING AND DISABILITY - Di Placito, Maria Lucia (Critical Disability Discourses, 2011)
<!--[if gte mso 9]> Normal 0 false false false EN-CA X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> The experience of disabled or ill mothers is a topic of interest that has been explored in a number of ways and within various research areas, including sociology, education, women/feminist studies, critical disability studies, and science-related fields (e.g., Davidson & Letherby, 2010; Dossa, 2009; Lewiecki-Wilson & Cellio, 2010; Malacrida, 2009; Vannatta, Grollman, Noll, & Gerhardt, 2008). Despite the common themes of mothering and disability, studies in this area can differ in their methodological approach. Drawing on the methodological inquiries and discussions of researchers such as, Devault (1990), Fontana and Frey (2005), Lincoln (1993), and Roulston, deMarrais, and Lewis (2003), I investigate how and why the interview approach operates well as a method of data collection when exploring the work of mothering and disability through a socio-feminist perspective. During this investigation, I briefly identify the analytical and theoretical issues associated with this topic, and how the interview can mitigate these limitations.